The reliability and validity of the arthritis impact measurement scales 2-short form adapted for Filipino patients with osteoarthritis - Alviar, Maria Jenelyn M.
OBJECTIVES: To develop a cross-cultural adaptation of the Arthritis Impact Scales 2-Short Form (AIMS2-SF) for Filipino patients with Osteoarthritis; and to determine its reliability and validity. To determine the quality of life (QOL) of Filipino patients with osteoarthritis according to the five domains specified in the cross-cultural adaptation of the AIMS2-SF. To determine the relationship of the socio-demographic and clinical characteristics with the quality of life. DESIGN: Cross-sectional. METHODOLOGY: A. Development of the AIMS-2SF Filipino version: A cross-cultural adaptation of the Arthritis Impact Measurement Scales 2-Short Form, "Pagsukat ng Kalagayan ng Pasyente na may Arthritis", was developed by forward/backward translation, committee review and pre-testing. B. Tests of reliability and validity: Three hundred patients with osteoarthritis as per ACR criteria seen in the Rehabilitation Medicine Out-patient Departments of Philippine General Hospital and Jose Reyes Memorial Medical Center were included in the study. Socio-demographic (age, sex, status, occupation, education attainment, income) and clinical variables (joint/s affected, area of involvement, visual analog scale score (VAS), duration of symptoms, number of painful joints, grip strength, walk time, number of co-morbid conditions) were recorded. The Filipino version of the AIMS-2 SF was administered to all subjects. Inter-item reliability, item-to-total reliability, and internal consistency analyses were performed. Content validity (content relevance and content coverage) was assessed by a panel of content experts. Convergent validity was evaluated by testing a priori-hypotheses. Construct validity was assessed by factor analysis.